Anomaly Bandwidth Usage Detection in LAN Islamic University of Riau using Wireshark Analyzer - Listia Rosa, Sri; Abdul Kadir, Evizal (International Journal of Engineering and Technology, 2018)
Increasing internet network traffic in a Local Area Network (LAN) will impact to internet access performance. Abnormal internet traffic monitoring system is very important to detect anomaly usage of internet bandwidth. In Islamic University of Riau (UIR) one of the issue related internet usage and normal method is by tapping a monitoring computer to the main terminal of LAN or source of internet provider. This research proposes a new method of monitoring system that gives detail information by using traffic behavior method and history of traffic connected, whereas detail information of internet bandwidth used is monitored for analysis. In this research case location is in Islamic University if Riau, Indonesia campus LAN area. Results shows graph of monitoring in day time because of student activities only in that time, various website and link access by students and staff in the campus be able to captured including duration with specific time. This method gives continues and accurate data to capture anomaly data use including Internet Protocol (IP) address of computer or device connected. The system help operator to give report related to internet usage and user who connected as well as data used in automatic system. Â